Implication And Application MBKM’s Curriculum In Education (Madrasah And Universities) - Dian Dian; Chyril Futuhana Ahmad; Fathur Riyadhi Arsal; Siti mahmudah (At-Ta'dib, 2023)
The Indonesian government has recently implemented a new education policy called "Kurikulum Merdeka". This policy aims to provide more flexibility and freedom for Madrasahs and teachers to develop their own curriculum and teaching methods that are better suited to the needs of their students. Kurikulum Merdeka is considered a departure from the previous centralized curriculum system, which was heavily focused on standardized testing and did not always reflect the diversity and local context of Indonesian society. This article aims to investigate the implications of Kurikulum Merdeka on Indonesian Madrasahs. The method used in this research was qualitative by collecting any literature related to Merdeka Belajar Curriculum. However, the implementer's attitude dimensions have a lower average value and require care. The implementer's attitude is crucial because support, resistance, and dedication are markers of the program's effectiveness. For teachers, lecturers, and students alike, MBKM is one of the crucial policies in the growth of higher institutions. There are eight Merdeka Learning Campus Merdeka programs, as shown by the findings, including: 1) student exchange, 2) apprenticeship/work experience, 3) teaching in educational establishments, 4) projects in villages, 5) research, 6) entrepreneurial endeavors, 7) independent study, and 8) charitable endeavors.